2004
DOI: 10.1111/j.1439-0272.2004.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone and vitamin E on the antioxidant system in rabbit testis

Abstract: The aim of the study was to investigate the effects of testosterone propionate and vitamin E on the antioxidant system in the testis. Thirty-two male New Zealand White rabbits were randomly divided into four groups. The first group was used as control. The second group was injected with testosterone propionate, the third group vitamin E and the fourth group vitamin E and testosterone propionate combination. All treatments were carried out during 6 weeks and oxidative parameters were evaluated in homogenized te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…In addition, we show a key role of c-Src in both genomic and nongenomic effects of testosterone in VSMCs. Our data corroborate previous studies showing that testosterone induces oxidative stress in rabbit and rat prostate 34,35 and is related to augmentation of blood pressure levels in different animal models of hypertension.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we show a key role of c-Src in both genomic and nongenomic effects of testosterone in VSMCs. Our data corroborate previous studies showing that testosterone induces oxidative stress in rabbit and rat prostate 34,35 and is related to augmentation of blood pressure levels in different animal models of hypertension.…”
Section: Discussionsupporting
confidence: 82%
“…If egg hormone treatment were to result in consistently higher nestling blood levels of testosterone or related steroids this would probably affect plasma total antioxidant capacity. It has been shown that high levels of circulating testosterone impair antioxidant enzymes in rat and rabbit testicular tissues (Chainy et al, 1997;Aydilek et al, 2004) [but see Peltola et al (Peltola et al, 1996)]. Moreover, high testosterone blood levels have recently been shown also to negatively influence red blood cell resistance to a free radical attack in adult zebra finch males (Alonso-Alvarez et al, 2007b).…”
Section: Effects Of Egg Treatmentmentioning
confidence: 99%
“…A number of studies have drawn the attention on the adverse reactions produced by some hormonal chemicals, with direct effects on the spermatogenetic function (4). Such results were reported after the administration of substances such hexestrol diacetate (5), dienestrol (6), nortestosterone decanoate (7) and estradiol benzoate (8). The studies were conducted on pubescent males belonging to several species of mammals: rats (3), mice (7), Guinea pigs (9), and rabbits (5).…”
Section: Introductionmentioning
confidence: 89%